Curtailing Unhealthy Consumption of Alcohol for Sustainable Development in India and South Africa - Marara, Praise; Rath, Seema; Sharma, Samridhi; Bosman, Sean James; Srinivas, Sunitha (Indian Journal of Pharmacy Practice)
Alcohol consumption has been a major contributor to the global burden of diseases, accounting for 3.3 million deaths, which is equivalent to 5.9% of all global deaths. Alcohol misuse is the fifth leading risk factor for premature death and disability, and is the top factor among people between 15 and 49 years. There are causal relationships between the harmful use of alcohol and incidences of both non-communicable diseases and infectious diseases such as STIs, including HIV/AIDS. In addition to health consequences, the harmful use of alcohol also causes significant social and economic losses to individuals and society. This article focuses on alcohol consumption in India and South Africa, and highlights the policies that have been adopted in both countries and discusses interventions that could be used to combat it. Though policies and interventions have been put into place, gaps exist because alcohol use is high, especially in South Africa, and continues to rise in both countries. Strategies to reduce the harmful use of alcohol include the adoption of national policies and educational interventions such as health promotion. To reduce the harmful use of alcohol, the World Health Organization Global Strategy provides an initial framework that countries can adopt. South Africa’s national policy follows this framework, while in India, alcohol remains a state/province controlled subject. A well formulated national policy on alcohol use, when implemented effectively, could have a positive effect on sustainable development.
Keywords: Harmful Use of Alcohol; Non-Communicable Diseases; Infectious Diseases; India; South Africa